Penerapan Simple Linear Regression Untuk Memprediksi Jumlah Kasus Covid Di Indonesia - Kurniawan, Agus; Kokanda, Kurniawan; Winderson (Journal of Digital Ecosystem for Natural Sustainability, 2021)
The rapid spread of covid has had many impacts on all people in the world. In Indonesia, the first case of COVID-19 was found in March 2020 and continues to spread until now. Many government efforts started from PSBB to PPKM and also several regulations in it to prevent the spread of this virus. So, by using the RStudio program and trying to execute the spread of COVID-19data with this simple linear regression method to predict the number of COVID-19cases to find out whether there will be a case increase in Indonesia on a certain date. Besides that, the result of the predicted data can be used for any purpose or it can also use to compare predictive data with actual data.